Model Intervensi Kolaboratif Keluarga-Sekolah dalam Mitigasi Dampak Negatif Gadget pada Anak dan Remaja - Keyla Syalsa Billa; Duna Izfanna; Pauly Demanda; Zahra Adelia Putri; Lala Cahya Kamila; Amanda Zulaikha Pulungan; Muhammad Iman Kurniawan (BUDIMAS : JURNAL PENGABDIAN MASYARAKAT, 2026)
This research responds to the crisis of excessive gadget use among Indonesian children and adolescents, which reaches 8-9 hours per day, far exceeding global recommendations. The study aims to formulate a holistic intervention strategy based on Islamic educational values, which has been lacking in the literature. We detected a gap between screen time recommendations and their implementation in the local context, as well as a lack of policy models in Islamic educational institutions to mitigate the negative impacts of gadgets. The activity was carried out through a participatory seminar entitled "The Positive and Negative Impacts of Gadget Use and the Urgency of Wise Use," featuring Islamic education experts. This method combined material delivery with interactive dialogue and involved 30 educators. We deliberately eliminated digital presentations and replaced them with printed modules and family activity sheets to ground the anti-gadget approach in concrete terms. Key findings revealed that gadget addiction, decreased children's focus, and parenting conflicts due to parental inconsistency were the dominant complaints among participants. The presenters introduced four main strategies: strengthening direct communication and empathy, access to structured encryption, developing children's potential without excessive technology, and parental collaboration through firmness and role modeling. Over 70% of participants actively shared their experiences and responded positively to this approach. Discussions yielded practical solutions such as agreed-upon device-free zones, enjoyable alternative activities, and alignment of parenting styles. The study concluded that the anti-gadget approach is not a rejection of technology, but rather a conscious effort to restore digital-human balance. Consequently, Islamic educational institutions need to establish curricular and extracurricular policies that strengthen collective parenting capacity. Future research will focus on developing a longitudinal intervention model and measuring the effectiveness of the anti-gadget policy at Melati Cidokom Elementary School in Bogor.